Meta-epidemiological assessment and evaluation of certainty of evidence in systematic reviews with meta-analyses of cognitive behavioral therapy and psychodynamic/psychoanalytic psychotherapy: an umbrella review protocol - Lerner, Rogério; Gonçalves, Bárbara; Dias, Caroline Martins; Gerotto, Júlia Benvenutti; Rufino, Tayane Aparecida Teizen; Aragão, Yasmin Meireles; de Arantes, Izabella Lopes (Frontiers in Psychiatry, 2025)
BackgroundPsychodynamic/psychoanalytic psychotherapy (PPT) and cognitive behavioral therapy (CBT) are two major therapeutic modalities widely used in clinical practice and supported by distinct theoretical and empirical bases. Persistent debate–particularly around PPT’s evidentiary strength–underscore the need to critically appraise the methodological quality and certainty of evidence of systematic reviews with meta-analyses (SRMAs) that underpin claims regarding its effectiveness, particularly in comparison with CBT.ObjectiveThis umbrella review will assess and compare the methodological rigor (AMSTAR-2) and certainty of evidence (GRADE) of systematic reviews with meta-analyses (SRMAs) of randomized controlled trials (RCTs) of CBT and PPT, published between 2015 and 2024.MethodsWe will search Embase, The Cochrane Library, PsycINFO, PubMed, and Web of Science for peer-reviewed SRMAs of RCTs of CBT and PPT across various mental disorders. Methodological quality will be assessed using AMSTAR-2, and their certainty of evidence will be evaluated using the GRADE system. Descriptive, correlational, and comparative analyses will examine associations between methodological quality, certainty of evidence, and reported SRMA-level effect patterns, and be used to synthesize the findings. Sensitivity analyses will address quality threshold, comparator class, psychiatric diagnosis, and quality thresholds; multiple testing will be corrected by Holm-Bonferroni.DiscussionBy evaluating and comparing the volume, methodological rigor, and certainty of evidence of SRMAs CBT and PPT, this umbrella review aims to contribute to the ongoing debate on evidence-based psychotherapy, inform clinical decision-making, guide future research, and support evidence-informed public health policy.Systematic Review RegistrationPROSPERO (CRD420250619644).